Anatomical and ultrastructural aspects of root and mycorrhiza of Anadenanthera peregrina (L.) Speg. var. falcata (Benth.) Altschul (Leguminosae-Mimosoideae) - Gross, Eduardo; Cordeiro, Lázara [UNESP]; Caetano, Flávio H. [UNESP] (Sociedade Botânica de São Paulo, 2003)
A. peregrina var. falcata form mutualistic symbiosis with arbuscular mycorrhizal fungus. An anatomical and ultrastructural study was carried out to analyze some aspects of this simbiotic association as well as some root features. The results evidenced the presence of fibers with non-lignified thicked secondary walls in the stele and sparse papillae on root surface. A. peregrina var. falcata mycorrhizas presented features of Arum-type (intercellular hyphae) and Paris-type (extensive coils) arbuscular mycorrhiza. Their general appearance with extraradical hyphae, intracellular coils, intercellular hyphae and arbuscules, is in agreement with arbuscular mycorrhizas of several plants. The ultrastructural observations showed that in intercellular hyphae and arbuscules vacuoles were dominant and that in rough endoplasmatic reticulum and small vesicles seems to be associated with arbuscule senescence process.

A. peregrina var. falcata forma simbiose mutualista com fungos micorrízicos arbusculares. Um estudo anatômico e ultra-estrutural analisou alguns aspectos dessa associação simbiótica bem como algumas características da raiz. Os resultados evidenciaram a presença de fibras com parede secundária espessadas não lignificadas no cilindro vascular e a presença de papilas esparsas na superfície da raiz. As micorrizas de A. peregrina var. falcata apresentaram características de micorriza arbuscular do tipo Arum (presença de hifas intercelulares) e do tipo Paris (presença de enovelamento de hifas). Seu aspecto geral com hifas extraradiciais, enovelamentos intracelulares de hifas, hifas intercelulares e arbúsculos seguiu o padrão encontrado nas micorrizas arbusculares de várias plantas. As observações ultra-estruturais demonstraram que as hifas intercelulares e os arbúsculos são bastante vacuolizados e que o retículo endoplasmático rugoso e pequenas vesículas parecem estar associados com o processo de senescência do arbúsculo.
Aspectos anatômicos e ultra-estruturais da raiz e micorriza arbuscular de Anadenanthera peregrina (L.) Speg. var. falcata (Benth.) Altschul (Leguminosae-Mimosoideae)
Keywords: Anadenanthera peregrina var. falcata; anatomy; mycorrhiza; root; ultrastructure; Anadenanthera peregrina var. falcata; anatomia; micorriza; raiz; ultra-estrutura